(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In this work, we explore group theory ideas implemented to biology and in selective systems of biology. Symmetry performs a notablerole in biology of bilaterians over radially symmetric bodies. The distinction between living and non-living organisms is best known.We concentrate on the group theory and abstract algebra covering the biology of molecular systems. We provide the applications ofgroup theory to cancer cells. We review applications to the cells cycle and explore how cells growing and forming cycles. We appliedgroup theory to Cancer Cells and present example to support the validity of the article.